Ketentraman Jiwa dalam Persepektif Al-Ghazali - Idrus H Ahmad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Allah did not create a soul in a perfect shape, unlike body which need time to be perfect. While soul will reach a perfect level through education, especially religious teachings that provide a guidance, counseling, leading and forming gradually or from one stage to the next stage. So that soul will grow stronger and well established to face any problems, by the end the soul becomes perfect, safe and secure. The human‟s soul has the potential of evil and goodness, where the badness will bring about a misery to one‟s life and a goodness thing will create the happiness in one‟s life. It‟s need an effort to remove and prevent of mental illness, such as takabbur, ria, These behaviors could be a barrier to go to the presence of God. According to al-Ghazali, one of the formulas to create a calm and serene soul is by rearranging a wide range of existing stations in Sufism as the essence of the kalam Ilahi. To reach a tranquility of life, according to alGhazali's, the people are always approaching Allah and remember Him along human‟s life.